Effects of drought and abscisic acid on peroxidase activity and growth in pepper plants. - Awad, Mohamed Hamad; Ismail, Mohd Razi (2001)
Pepper plants. Capsicum annuum L. cultivar MCl2 were used i this investigation to determine whether five days treatment applying 50 m110,r ABA per day to the soil surrounding the pepper roots would affect the peroxidase activity in the elongation zone the third leaf of the plant. Seven days after the beginning of the treatment the cell wall peroxidase activity had increased in both the ABA treated plants and the droughted plants 136.4% and 172. %from their original cell wall peroxidase activities respectively. Cytoplasmic peroxidase activity had increased in both ABA and droughted plants 44% and 72% from their original cytoplasmic peroxidase activity respectively. Leaf growth rate had decreased in both the ABA treated plants the droughted plants. Over the six day period the ABA plant leaves showed about 40% decrease in growth rate and the droughted plants leaves exhibited an 59.2% decrease in growth rate. The results indicate that ABA brings about an increase in peroxidase activity and may aid in the cessation of cell expansion. As the drought plants had higher levels of cell wall and cytoplasmic peroxidase activity and a greater decrease in leaf growth rate than the ABA plants, this suggest that ABA is not the only factor which increase peroxidase activity. though it may be the major factor.